Presence of white-nose syndrome in bats from Southern Mexico - Gabriela Elena Medina-Cruz; Carla Gabriela May-Mutul; Paola Nicté López-González; Lizbeth Josefina González-Herrera; Javier Enrique Sosa-Escalante; Angel Rodríguez-Moreno; Judith Castellanos-Moguel; Héctor David Martínez-Tamayo; Gabriel Gutiérrez-Granados; Víctor Sánchez-Cordero; Miguel Briones-Salas (PLoS ONE, 2025)
White-nose syndrome (WNS), caused by the fungus Pseudogymnoascus destructans, is increasingly causing high mortality in North American vespertilionid bats. This fungus has become widely established, appearing in bat populations from Asia, Europe and North America, including in the state of Texas, U.S., creating a high potential for dispersal into neighboring Mexico. In this study, we collected samples from 11 captured individuals and 15 carcasses of Myotis velifer, Dermanura azteca, Pteronotus parnellii, Desmodus rotundus, Balantiopteryx plicata and Anoura geoffroyi species of bat that were living in a cave in southern Mexico. Using morphological and molecular techniques, we found P. destructans in vespertilionid and emballonurid bats, including 9 individuals of M. velifer (8) and P. parnellii (1), and in 1 carcass of B. plicata. Captured individuals and carcasses showed injuries mostly to their wings, patagium and rostrum. Thermotolerance experiments confirmed that P. destructans can grow at a wide range of temperatures (5–28 °C), making this fungus a risk to bat species in a wide range of habitats, including the tropical environments of southern Mexico. This study evidences the presence of P. destructans in southern Mexico, validating the need for a monitoring program and education to inform communities of the potential detrimental that P. destructans may have on other populations and species of bats in a Mesoamerican biodiversity hotspot.